Effect of dent defects on the collapse pressure of sandwich pipes. (January 2022) - Yu, Jianxing; Xu, Weipeng; Chen, Nian-Zhong; Jiang, Sixuan; Xu, Shengbo; Li, Haoda; Han, Mengxue
Abstract: This paper aims to assess the effect of dent defects on the collapse pressure of sandwich pipes under external pressure. A new pipe-making process is proposed, and its ability to resist external loads is investigated. The result shows that the collapse pressure of the sandwich pipe is 76.46%–99.95% higher than that of a single-wall pipe in the same dent defect, and the buckling propagation pressure is 100% higher than the sum of the inner and outer pipes. Otherwise, the influence of the dent on the sandwich pipe is weakened. The pipe consists of two steel pipes and a polypropylene pipe bonded together by one-millimetre thick epoxy resin to form a sandwich pipe. Seven specimens with varying degrees of defects were investigated to obtain their collapse pressure, where four specimens are sandwich pipes. Additionally, a numerical model was established and validated, and systematic parametric studies were carried out to supplement the test results. The experimental and numerical results show that the collapse pressure of the sandwich pipe is significantly influenced by the dent defect. Based on the parametric study, the main parameters that affect the collapse pressure of sandwich pipes are obtained. The relationship between the collapse pressure and the geometry of the sandwich pipes was analysed. The research shows that dent defects have a significant effect on the collapse pressure of sandwich pipes and that reducing the thickness-to-ratio of the inner pipe and the friction between layers is an effective method to improve the collapse pressure of defective sandwich pipes. Highlights: A new manufacturing method for the sandwich pipe is proposed and the polypropylene pipe is chosen as the core layer. 7 collapse tests of pipes subjected to external pressure have been carried out. The effect of dent defects on the collapse pressure of sandwich pipe under external pressure was experimentally investigated. The difference of the cross-section and collapse and buckling propagation of the sandwich pipe are analysed. A numerical simulation method was proposed.